Decorative Motifs and Periodization of Badut Temple: Comparative Review of Art Forms with The Temples of Central JavanesePeriod: Ragam Hias dan Periodisasi Candi Badut: Tinjauan Perbandingan Bentuk Seni dengan Candi-Candi Periode Jawa Tengah - Pradnyawan, SS., M.A. , Dwi (BRIN, 2024)
There are two known arguments of the periodization of Candi Badut. Firstly, grouping this temple as part of the oldest temple in Java, covering the early to mid-8th century AD. Secondly, positioning this temple in the period of later half of the 9th to early 10th centuries AD. The argument that Candi Badut belongs to the oldest temples in Java’s group is more widely accepted. Thus, this article discusses art analysis of Candi Badut as periodization aspect. The analysis conducted towards decorative or ornamental motifs through the comparative method with the temples in the Central Java period. The research result shows that Candi Badut has several distinguished decorative motifs, such as the kinnara-kinnari motif, the antefix motif, and the decoration above of the Kala motif. Those motifs are considered evidence that Candi Badut belongs to the later half of the 9th century to the early 10th century AD.